Compensation irradiance and depth limits of transplanted eelgrass (Zostera marina) along a eutrophication gradient - Banke, Timi L.; Steinfurth, Rune C.; Barnewitz, Anders; Nielsen, Benjamin; Jones, Owen R.; Flindt, Mogens R. (Frontiers in Marine Science, 2025)
The global seagrass decline has prompted numerous restoration efforts to reverse current trends. Yet, restoration efforts are challenged by ecological feedbacks and prevalent stressors. Identifying these stressors and the thresholds where seagrass shoot production becomes negative is vital to improve site-selection procedures and increase restoration success. In this study, we investigated the ecological compensation irradiance (ECI) and depth limit of eelgrass (Zostera marina L) transplants along a eutrophication gradient. This was accomplished by establishing eelgrass transplants along eutrophication and depth gradients while continuously measuring benthic Photosynthetically Active Radiation (PAR). High-temporal monitoring of shoot count allowed precise estimates of shoot production, which was applied to modified photosynthesis-irradiance curves, thereby estimating the ECI. The ECI fell within the interval 2.6 – 9.8 E m-2 d-1 and responded distinctly along the eutrophication gradient, decreasing as eutrophication and nutrient-derived stressors were alleviated. The depth limits were concurrently controlled by irradiance and ECI and similarly responded along the eutrophication gradient, increasing from 1.1 m at the innermost station to 4.7 – 5.6 m at the two outermost least eutrophic stations. The results demonstrate that the ECI of eelgrass varies according to the local environment, with implications for habitat suitability assessment and site selection procedures in restoration efforts.